Dynamics Of Citizenship Literacy Perception Among Indonesian Senior High School Students - Iin Nurul Khoiriyah; Anan Sutisna; Awaluddin Tjalla (Eduvest - Journal of Universal Studies, 2025)
This study explores the perception of high school students towards civic literacy in Indonesia, covering four literacy domains: civic institutions and systems, civic principles, civic participation, and civic roles and identities. Using phenomenological qualitative methods and thematic content analysis, this study explores how students' social interactions, personal histories, and social values shape their understanding of citizenship. Data were collected through in-depth interviews, participatory observations, and documentation studies. Results show that students have a varied understanding of the system of government, democratic values, social and political participation, and civic identity and role, indicating a significant influence of civic education on their civic literacy. This research recommends the integration of practical experience and real application in education to strengthen civic literacy.